2021
DOI: 10.21037/atm-20-6115
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center survey on the postpartum mental health of mothers and attachment to their neonates during COVID-19 in Hubei Province of China

Abstract: Background: There is an emerging literature on the mental health of both pre-and post-partum mothers during the coronavirus disease 2019 (COVID-19) pandemic.Methods: As of April 1, 2020, 23 mothers confirmed with COVID-19, 15 mothers suspected with COVID-19 but with negative polymerase chain reaction tests, and 33 mothers without COVID-19 (Control Group) were recruited for a study from Hubei Province in China. The Maternal Postnatal Attachment Scale (MPAS), the Zung Self-rating Anxiety Scale, and the Zung Self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
0
14
0
2
Order By: Relevance
“…In Cojocaru’s study [86] , most COVID-positive mothers still opted to room in with their newborns and continue with skin-to-skin contact. In contrast, Peng and colleagues [87] reported a longer period of mother-infant separation and lower infant attachment score among COVID positive mothers than COVID negative mothers did. The concerns and difficulty of neonatal separation faced by COVID positive mothers were flagged in qualitative studies, where mothers mentioned a lack of updates on their baby and the fear of infecting their baby [83] , [88] .…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In Cojocaru’s study [86] , most COVID-positive mothers still opted to room in with their newborns and continue with skin-to-skin contact. In contrast, Peng and colleagues [87] reported a longer period of mother-infant separation and lower infant attachment score among COVID positive mothers than COVID negative mothers did. The concerns and difficulty of neonatal separation faced by COVID positive mothers were flagged in qualitative studies, where mothers mentioned a lack of updates on their baby and the fear of infecting their baby [83] , [88] .…”
Section: Resultsmentioning
confidence: 79%
“…In Liu’s study [70] , 45.8% of mothers did not have a support person during birth, and another study [49] found lower birth satisfaction in mothers who did not have a birth support partner than those who had. Qualitative findings often reported negative experiences of mothers who did not have a support partner present during labour [30] , [36] , [39] , [45] , [46] , [61] , [66] , [68] , [87] . Some mothers perceived the absence of a birth partner as a loss of reassurance and advocate [55] , [78] while others felt alone, stressed, anxious, and that their mental health was at stake [44] , [45] , [52] , [65] .…”
Section: Resultsmentioning
confidence: 99%
“…Collins, Fruhman [ 20 ] reported that postpartum depression among COVID positive mothers is significantly greater than COVID negative women, with the odds ratio of 3.7. In Chinese population, Peng, Zhang [ 21 ] stated that COVID positive mothers have lesser Maternal Postnatal Attachment Scale score. However, the anxiety and depression scores among COVID confirmed, suspected and control cases did not differ significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies across the world have reported mixed findings on the mental health and well-being of perinatal women during COVID-19 (11)(12)(13)(14)(15)(16)(17)(18). Six studies in postpartum mothers across the world, North-eastern Italy, Belgium, China, and America have found increased depressive and anxiety symptoms (11,12,(14)(15)(16)(17), whilst another study in postpartum women in Japan reported normal levels of mental health and well-being (13). In addition, emerging evidence suggests the amount of physical activity women across the world partake in is also an important factor when considering maternal mental health during the pandemic (11).…”
Section: Introductionmentioning
confidence: 99%